Synthesis and Antibacterial Activity of Some Newer Thiazolidine-2,4-Dione Derivatives - Amit Kumar; Nitin Mittal; Mukesh Gupta; Shikha Sharma (Journal of Biomedical and Pharmaceutical Research, 2023)
Thiazolidin-2,4-diones were intensively studied for its antidiabetic property in 1982. Thiazolidin-2,4-diones have also been demonstrated to possess different biological activity like anticancer, anti-HIV, antitumor, antimicrobial, antiviral and antiproliferative activity. 3-Benzoyl-5-(substituted benzylidine)-thiazolidin-2,4-diones and 3-p-Tolyl-5-(substituted benzylidine)-thiazolidin-2,4-diones have evaluated as structurally novel antimicrobials. A series of 5-[(SubstitutedPhenylamino)benzylidine]thiazolidine-2,4-dione derivatives 17(a-j) were synthesized by nucleophilic substitution reaction of (Z)-5-(2-Fluororobenzylidin)-thiazolidin-2,4-dione with various benzaldehyde derivatives and (Z)-5-(2-Fluororobenzylidin)-thiazolidin-2,4-dione were synthesized by condensation of thiazolidin-2,4-dione with p-fluorobenzaldehyde. The reaction was monitored by TLC on silica gel G plates and the final compounds were purified by recrystalization from ethanol.The structure of newly synthesized compounds 17(a-j) were confirmed by FTIR, 1H NMR, EIMS spectral analysis and elemental analysis. All the synthesized compounds were screened for antibacterial. Antibacterial activity was screened against Gram positive (B. subtilis, P. aeruginosa) and Gram negative bacteria (E.coli, S. aureus) by paper disc diffusion method, using nutrient agar medium. The compounds substituted with hydroxyl, methoxy, nitro and chloro on aryl ring attached with thiazolidin-2,4-dione showed good antibacterial activity. The synthesized compound: 17c and 17d showed significant antibacterial activity against gram positive bacterial strain B.subtilis and S.aureus and compound 17g showed significant antibacterial activity against gram negative bacterial strains E.coli and P.aeruginosa. The zone of inhibition was compared with standard drugs ciprofloxacin at 50 μg/ml concentration.